Meta‐Analytic Research in Management: Contemporary Approaches, Unresolved Controversies, and Rising Standards. (12th December 2018) - Combs, James G.; Crook, T. Russell; Rauch, Andreas
Abstract: Early meta‐analyses in management research sought primarily to resolve seemingly conflicting findings by estimating a relationship's population‐level effect size. Since then, management researchers have adopted increasingly sophisticated approaches that permit new theorizing, testing and comparing sophisticated models, and identifying boundary conditions. We summarize three of these approaches – i.e., qualitative meta‐analysis (QMA), meta‐analytic structural equation modeling (MASEM), and meta‐analytic regression analysis (MARA) – along with the special issue papers that adopt each approach. We conclude by raising three unresolved controversies that we believe deserve more attention and by offering our thoughts about how to maximize a meta‐analytic study's chances for publication and impact.